WOMEN’S LANGUAGE ON WOMEN’S COMMENTARY : SRIKRISHNAKIRTAN POETRY/ নারীর বয়ানে নারীর ভাষ্য : শ্রীকৃষ্ণকীর্তন কাব্য (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2025)
Like other female-led poems of the Middle Ages, women have also gained prominence in Baru Chandidas' 'ShriKrishnakirtan'. There is also own dialogue of women. Therefore, the analysis of women's language in the context of their own dialogue deserves a discussion. The two main women whose dialogues cover a wide range in the poem under discussion are - Radha and Barai. Numerous differences are observed between the words of women and men throughout the poem. Where the tone of women is soft and pleading, in most cases the seriousness of men is evident. Where the male character Krishna expresses his thoughts directly and clearly, the female characters, in most cases, resort to deception, keeping in mind the knowledge of time, and present them in a very elaborate manner. Similarly, various topics used in the words of Radha and Barai have emerged, which are distinct from the male language. The abundance of two-syllable and phonetic words, the dramatic presentation of words, the abundance of proverbs and sayings, the use of similes, etc., are used uniquely in women's language. And in the main discussion, all these issues have been discussed extensively with examples. In this context, it can be seen that women's language has moved away from men's language and has taken its place as a separate dialect. In the poem 'Shrikrishnakirtan', a description of women's language in early-Central Bengal has been developed through the women's own narration.
Keywords: women’s distinct language; women’s commentary; stereotype; communication style; language; men; women; women’s; presentation attitude